Does excessive sovereign debt really hurt growth? A critique of This time is different, by Reinhart and Rogoff - Yeva Nersisyan; L. Randall Wray (Levy Economics Institute of Bard College, 2010)
The worst global downturn since the Great Depression has caused ballooning budget deficits in most nations, as tax revenues collapse and governments bail out financial institutions and attempt countercyclical fiscal policy. With notable exceptions, most economists accept the desirability of expansion of deficits over the short term but fear possible long-term effects. There are a number of theoretical arguments that lead to the conclusion that higher government debt ratios might depress growth. There are other arguments related to more immediate effects of debt on inflation and national solvency. Research conducted by Carmen Reinhart and Kenneth Rogoff is frequently cited to demonstrate the negative impacts of public debt on economic growth and financial stability. In this paper we critically examine their work. We distinguish between a nation that operates with its own floating exchange rate and nonconvertible (sovereign) currency, and a nation that does not. We argue that Reinhart and Rogoff's results are not relevant to the case of the United States.
Keywords: E60; E61; E62; E64; E69; E32; O40; E31; 330; government debt; government deficit; sovereign default; Reinhart and Rogoff; economic growth; inflation; modern money